Consistent linkage of dominantly inherited osteogenesis imperfecta to the type I collagen loci: COL1A1 and COL1A2. - Sykes, B; Ogilvie, D; Wordsworth, P; Wallis, G; Mathew, C; Beighton, P; Nicholls, A; Pope, F; Thompson, E; Tsipouras, P (University of Chicago Press, 1990)
The segregation of COL1A1 and COL1A2, the two genes which encode the chains of type I collagen, was analyzed in 38 dominant osteogenesis imperfecta (OI) pedigrees by using polymorphic markers within or close to the genes. This was done in order to estimate the consistency of linkage of OI genes to these two loci. None of the 38 pedigrees showed evidence of recombination between the OI gene and both collagen loci, suggesting that the frequency of unlinked loci in the population must be low. From these results, approximate 95% confidence limits for the proportion of families linked to the type I collagen genes can be set between .91 and 1.00. This is high enough to base prenatal diagnosis of dominantly inherited OI on linkage to these genes even in families which are too small for the linkage to be independently confirmed to high levels of significance. When phenotypic features were compared with the concordant collagen locus, all eight pedigrees with Sillence OI type IV segregated with COL1A2. On the other hand, Sillence OI type I segregated with both COL1A1 (17 pedigrees) and COL1A2 (7 pedigrees). The concordant locus was uncertain in the remaining six OI type I pedigrees. Of several other features, the presence or absence of presenile hearing loss was the best predictor of the mutant locus in OI type I families, with 13 of the 17 COL1A1 segregants and none of the 7 COL1A2 segregants showing this feature.